A case study on network performance analysis in Jabatan Agama Islam Selangor (JAIS) / Norkhairulbariah Omar - Omar, Norkhairulbariah (Faculty of Information Technology and Quantitative Sciences, 2006)
This project is about network performance analysis at Jabatan Agama Islam Selangor (JAIS). At Jabatan Agama Islam Selangor (JAIS) their network administrator always receives complaints about network slowness. The situation to show this problem is users in JAIS have problems accessing Internet. They had to wait to open or retrieved any websites. The network administrators in JAIS believed that most of the staff in JAIS access the unauthorized website provided is not enough to support the users demand. JAIS determine unauthorized website in this case specific for user at JAIS using internet not for doing their work but accessing entertainment website like download song, video and radio. As for that, the purpose of this thesis is to study network performance analysis at JAIS focus on incoming traffic and outgoing traffic for relate with used switch to connect user to the server and separate system application and database, network adapter CAT 6 UTP cable analysis at JAIS and users activity accessed website analysis at JAIS to detect user access unauthorized website and also could help the network administrator reducing network congestion. In this case, we could specific to analysis about what the staff activity who using Internet using Squid software and SARG (Squid Analysis Report Generator) software.